RESEARCH ON THE BODY-MASS INDEX OF THE BODY AND THE BODY CIRCUMFERENCE IN THE CURRENT SECTION OF THE EQUAL ROTATION MOMENTS OF THE UPPER AND LOWER PART OF THE BODY - A. Atanasov; N. Pirovski; D. Valev (Trakia Journal of Sciences)
The bed-scales determine the section in which the torques of the upper and lower body is balanced. In this section, body circumference is measured and a relationship is sought between body circumference and body mass parameters (M, kg), body height (H, m), and body mass index (BMI, kg/m2 ). Aim of the study: Investigate the relationship between the circumference of the body in the cross section of the equal torques of the upper and the lower body and the body mass index of the body. Results: 64 people between the ages of 18 and 28 were examined. The high correlation coefficient between the body circumference and body mass and BMI, as well as low correlation coefficient between body circumference and body height were obtained. Conclusions: There is no statistically significant relationship between body circumference and height. At different body heights, equal body circumferences can be observed.